2008
DOI: 10.1111/j.1475-4754.2008.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

ARCHAEOMAGNETISM IN ARCHAEOMETRY— A SEMI‐CENTENNIAL REVIEW*

Abstract: The journal Archaeometry and its first co‐editor Martin Aitken played key roles in the development of archaeomagnetism. This paper briefly reviews all papers published in Archaeometry, and a few others, dealing with archaeomagnetic secular variation, archaeomagnetic dating, archaeointensity studies and related applications of magnetic studies to archaeology, to indicate some of the major developments over the past 50 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Thus, knowledge of the characteristics of the ancient geomagnetic field can provide important information in order to better understand and constrain the processes related to the evolution of the Earth's deep interior. On the other hand, the archaeologist stands to learn about the relative and absolute dating of baked features (Tarling 1983; Eighmy and Sternberg 1990; Sternberg 2008). Recent investigations also suggest a connection between the geomagnetic field and climatic changes during the Holocene (Courtillot et al .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, knowledge of the characteristics of the ancient geomagnetic field can provide important information in order to better understand and constrain the processes related to the evolution of the Earth's deep interior. On the other hand, the archaeologist stands to learn about the relative and absolute dating of baked features (Tarling 1983; Eighmy and Sternberg 1990; Sternberg 2008). Recent investigations also suggest a connection between the geomagnetic field and climatic changes during the Holocene (Courtillot et al .…”
Section: Introductionmentioning
confidence: 99%
“…Environmental magnetic parameters have been proposed to be useful for assessing chert quality, distinguishing source areas, and identifying heated samples in the archeological record (Borradaile et al, 1993(Borradaile et al, , 1998Thacker and Ellwood, 2002;Sternberg, 2008). We discuss our results from the BCB chert types in light of these three main issues, and consider first an additional aspect (type and origin of magnetic minerals in chert) that has not been addressed in previous archeo-magnetic studies.…”
Section: Discussionmentioning
confidence: 80%
“…They have been also applied in archeology for discriminating obsidian and other raw material of archeological interest such as chert and flint (McDougall et al, 1983;Tarling, 1990;Church and Caraveo, 1996;Borradaile et al, 1998;Thacker and Ellwood, 2002;Sternberg, 2008). Studies focused on chert samples have already shown the usefulness of rock magnetic properties to establish the degree of chert purity and to assess the provenance of some chert types (see Borradaile et al, 1993Borradaile et al, , 1998Thacker and Ellwood, 2002;Sternberg, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory demagnetization methods are designed to recover the declination and inclination of the ancient magnetization by a series of demagnetization steps. This procedure sheds light on the processes involved in the ancient heating events (Gallet et al, 2009;Goulpeau, 1994;Hassul et al, in press;Lanos, Kovacheva, & Chauvin, 1999;Shaar et al, 2016;Sternberg, 2008;Sternberg & McGuire, 1990;Sternberg et al, 1999).…”
Section: Archaeomagnetismmentioning
confidence: 98%